Implikasi Murtad terhadap Keabsahan Perkawinan: Analisis Komparatif Empat Mazhab - Deris Arista Saputra; Zul-kifli Hussin (Yayasan Syamil Quran Nunukan, 2026)
This study examines the implications of apostasy on the validity of marriage from the perspective of the four major schools of Islamic jurisprudence, in light of the increasing number of religious conversion cases that raise family law issues in Indonesia. The aim of this research is to comparatively analyze the views of the Hanafi, Maliki, Shafi‘i, and Hanbali schools regarding the legal status of marriage after apostasy and its relevance within the context of national family law. The method employed is a Narrative Literature Review with a qualitative approach based on content analysis of classical fiqh literature and contemporary academic studies. The findings indicate fundamental differences among the schools in interpreting the validity of marriage and its legal implications; however, Indonesian Islamic law tends to adopt the principle of maslahah to uphold family justice and the protection of children.